Loading Eccentricity Issue on the Performance of Reinforced Concrete Columns - Mohammed, Kachalla (ARID ZONE JOURNAL OF ENGINEERING, TECHNOLOGY AND ENVIRONMENT, 2019)
Column is a structural element that transmits floor and beam loads to the foundation safely if properly designed. It is mostly loaded axially or eccentrically at the column-beam interface. Although several research articles are available on column performance (both eccentric and axial), but there is a behavioural challenge on a column loading position parallel to the axis in relation to the flexural reinforcement requirement for Reinforced Concrete (RC) column. This paper looks inward to address the challenge by providing an understanding on the complete behaviour of RC Column flexural requirement in relations with load and its point of application for both short and slender columns. This study uses a numerical data for the column analysis under varied loads and eccentricities values, and numerical deformation and stresses determination using ABAQUS. The Finite Element analysis (FEM) result indicates that increasing column axial load leads to an anticipated higher flexural reinforcement to enhance the column capacity, and is rational. Additionally, the established behaviour between the flexural reinforcement requirement and loading eccentricity for a rectangular column can be predicted easily using established linear relations for both column types considered in this study. Moreover, the Finite Element Method analysis result for the short column similarly indicates an interesting relationship where 16 % change in load value will translate to about 16 % change in deformation value irrespective of either axial or eccentrically loaded points.